An Ecofriendly Systhesis of 4-Thiazolidinone Derivative Using Tributylammonium Bromide Under Microwave Irradiation (Biological Sciences - PJSIR, 2009)
A series of new compounds 5-benzylidene-3-(4-methylphenyl)-2-(phenylimino)-4-thiazolidinone were synthesized by adopting environment friendly microwave irradiation methodology, their structures and in vitro antibacterial and antifungal activities are reported.The synthesized compounds exhibited different levels of antibacterial activities. Three compounds showed broad spectrum antibacterial activity.